Analisis Studi Literatur Pengkajian Algoritma Dan Pemrograman Mahasiswa Di Revolusi Industri Teknologi Pada Jurusan Pendidikan Matematika - Miftah Khairiyah SM; Yahfizham Yahfizham (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Particularly in the context of the technological industrial revolution, information technology is developing more quickly. We cannot prevent technological development in this life because it will inevitably follow scientific advancements in science. Educational technology has the power to transform traditional teaching methods into innovative ones. Even though the term "educational technology" has a very broad definition, it is frequently assumed to refer only to electronics or other technical tools. For this reason, we will talk more about educational technology in this article, particularly as it relates to its development in the context of science's rapid advancement. as well as society culture and technology Programming breakthroughs have virtually eliminated the need for manual implementation Our work and interests these days often stress our proficiency with computers. Logical thinking is crucial to the development of this revolution in order to comprehend its components, particularly the interconnectedness of computer programming algorithms and mathematics. In order to ascertain the actualization of this programming procedure, the literature analysis method was employed in the composition of this work. The sources for this article's collection included books and a number of earlier publications, the titles of which were created using bibliometric techniques. Thus, it is believed that the development of technological knowledge can proceed without hiccups with the involvement of algorithmic programming so that students can enhance the caliber of the amalgamation of technological information in the industrial revolution.